School Operational Assistance Management to Lighten School Burden: A Literature Review - Anugrah Anugrah; Widyatmike Gede Mulawarman; Nurlaelah Nurlaelah (EduLine: Journal of Education and Learning Innovation, 2022)
This paper aims to discuss the management of school operational funds in an effort to ease the school's burden. This study uses a literature review method with narrative analysis to deepen knowledge about the management of school operational funds. The data was obtained through the process of collecting written documents regarding the management of educational operational assistance from previous researchers and writers as well as documents of applicable laws and regulations. The results of this study can be drawn several conclusions: (1) school financial receipts and expenditures must be reported and accounted for regularly in accordance with applicable regulations. Budget reporting and accountability from parents and the community are carried out in detail and transparently according to the source of funds; (2) School Operational Assistance in practice is very helpful in realizing the quality of education. Nevertheless, the operational assistance must be appropriately managed and closely monitored by various parties so that its usefulness is in accordance with its primary duties and functions; (3) the preparation of school budgets and expenditures is a barometer in the financial managerial process in schools. Recommendations that can be given are to the manager of the school operational assistance program to further maximize the school active assistance program because this is one of the government programs that can assist the community in getting better educational services so that in its implementation in the field, more optimal management is needed so that the objectives and the benefits that can be obtained from this application can be channeled more optimally as well.